2019
DOI: 10.7717/peerj.6773
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced social inequality in health-related factors and quality of life in women and men from Austria who are overweight or obese

Abstract: Background The burden of social inequalities in health as well as the association between obesity with morbidity and mortality is a worldwide problem. Therefore, the aim of our study was to investigate health-related factors, health, and quality of life in Austrian women and men with normal weight, overweight, and obesity with a different socioeconomic status (SES) based on actual data from 2015. Methods This representative population-based study was based on self-reported data of 15,338 Austrian adults (8,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…In their non-disease-specific sample they found that obese individuals in lower SES group had lower HRQL than those of normal weight in the same SES group, and had lower HRQL compared to those in higher SES groups with the same weight. Subsequent studies confirmed these findings and found both moderator effects [ 60 , 61 ] and mediator effects for obesity/ BMI [ 62 ] regarding the relationship SES and quality of life.…”
Section: Discussionmentioning
confidence: 82%
“…In their non-disease-specific sample they found that obese individuals in lower SES group had lower HRQL than those of normal weight in the same SES group, and had lower HRQL compared to those in higher SES groups with the same weight. Subsequent studies confirmed these findings and found both moderator effects [ 60 , 61 ] and mediator effects for obesity/ BMI [ 62 ] regarding the relationship SES and quality of life.…”
Section: Discussionmentioning
confidence: 82%
“…Ressalta-se que a maioria das mulheres tinha até o ensino médio, o que abre um leque de ocupações com menor retorno salarial. A ocupação, assim como a educação, representam meios de acesso à renda e a serviços sociais básicos e relacionam-se diretamente com a pior autoavaliação do estado de saúde (19) . Estudos apontam que o nível escolaridade e renda baixa, assim como a moradia em áreas residenciais pobres estão associados a pior percepção de saúde e, consequentemente, ao aumento do risco de doenças (20)(21) .…”
Section: Discussionunclassified